Petróleo, royalties e Estado: desempenho da elite política e mídia capixabas, do "boom" das commodities ao impasse federativo sob a lei 12.734/2012 (2003- 2013) - Souza, João Paulo dos Santos de (2023)
The state of Espírito Santo played a central role in the federative impasse involving the dispute over oil royalties, a prominent event on the national agenda that mobilized both the media and Capixaba politics in the transition to the 2010s. This study focuses on events between the discovery of oil reserves in the pre-salt layer, announced in 2007, and March 2013, when Law 12.734/2012 was approved and subsequently litigated. The research investigates the participation of the Capixaba delegation through congressional articulations and pronouncements, as well as the commotion and discursive struggle waged by the main local newspapers, A Gazeta and A Tribuna. The main objective is to analyze historical narratives and uses of the past by various sectors and social segments, highlighting the implicitly promoted “sense of overcoming backwardness” by state elites (NASCIMENTO, 2016; 2018). To theoretically underpin this research, we turn to concepts such as backwardness, elites, and identities, framed in references such as habitus and political field, and incorporating elements of the new political history. Regarding the methodology, we adopt the content analysis developed by Laurence Bardin, using software for coding and digital treatment of printed sources, as well as syntactic analysis through programming. These approaches are essential for research that fits into the fields of History and Digital Humanities.